Erzeugung von Strom und flüssigen Kraftstoffen mit geringem Carbon Footprint. Issue 1 (16th January 2018) - Machhammer, Otto; Maaß, Hans‐Jürgen; Bode, Andreas
Abstract: The use of existing coal‐fired power plants enables the production of electricity and liquid fuels with low carbon footprint. Three process combinations are compared. Electricity is generated by the power plant and CO2 from the offgas is hydrogenated to liquid fuels with hydrogen. H2 is produced by water electrolysis or methane pyrolysis. Compared to electrical power from a coal‐fired power plant and fuel from an oil refinery, which is used as reference, CO2 emissions can be reduced in case that hydrogen comes from a windpowered water electrolysis or from a methane pyrolysis.